2013
DOI: 10.1093/ajh/hpt106
|View full text |Cite
|
Sign up to set email alerts
|

DASH Diet Score and Distribution of Blood Pressure in Middle-Aged Men and Women

Abstract: The observed associations indicate that the findings are consistent with the hypothesis that adherence to DASH-equivalent diet can reduce BP at the population level. Public policy promoting a DASH-style healthy diet could have a significant impact on population health by reducing average BP in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 32 publications
5
42
0
2
Order By: Relevance
“…It is well‐known that ambulatory BP monitoring (ABPM) provides the most accurate data on BP homeostasis . However, we identified only one study conducted in nondiabetic patients that demonstrated an inverse association of the adherence to the DASH diet with BP as measured by ABPM …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is well‐known that ambulatory BP monitoring (ABPM) provides the most accurate data on BP homeostasis . However, we identified only one study conducted in nondiabetic patients that demonstrated an inverse association of the adherence to the DASH diet with BP as measured by ABPM …”
mentioning
confidence: 98%
“…15 However, we identified only one study conducted in nondiabetic patients that demonstrated an inverse association of the adherence to the DASH diet with BP as measured by ABPM. 16 The long-term BP beneficial health effect of walking has already been demonstrated in patients with type 2 diabetes 17 and over 10,000 steps per day have been recommended for these patients. 18 A cross-sectional study conducted in patients with type 2 diabetes demonstrated that each increment of 1000 steps per day was associated with a small decrease in systolic and diastolic office BP in women.…”
mentioning
confidence: 99%
“…Breakdown of nutrient intake in the two groups is presented in Table 4, difference tests showed that there was no difference in nutrient intake in the hypertension and normal blood pressure groups in all components of nutrients assessed on the DASHlike diet (p≥0.05). Harrington et al (2013) reported that adherence to a diet based on the recommended DASH diet can reduce blood pressure and the results of a systematic review by Saneei et al (2014) also explained that the DASH diet can reduce blood pressure, both in systolic and diastolic. Our study found that the quality of the DASH-like diet in both groups were low, thus it can not prevent hypertension in the hypertension DASH-like diet and mental emotional disorder group.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have proven that DASH diet improved blood pressure and gave impact to cardiovascular disease (Fung et al 2008;Ridhwan et al 2012;Harrington et al 2013;Saneei et al 2014). Rahadiyanti et al (2015) developed a scoring system for the DASH-like diet in Indonesia, which measured the quality of diet from nine Islami et al…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional analysis of 2,046 patients from the Dietary Approaches to Stop Hypertension (DASH) study those who were most adherent to the DASH diet had the lowest blood pressures 25 . Further, baseline high intake of F&V was associated with lower rates of developing hypertension after 13 years of follow-up in a cohort study of middle and older age women, although the effect was small 7 .…”
Section: Discussionmentioning
confidence: 99%